SISTEM INFORMASI VARIAN ANGGARAN FLEKSIBEL PADA CV. ACTIVE PRODUCTION MAKASSAR - Mirza Wirawan M; Afifah; Ahyar Muawwal (STMIK KHARISMA Makassar, 2019)
Active Production Makassar is a company engaged in services offering MICE (Meeting, Incentives, Conferences, Exhibition). In the implementation off the event, the organizers did a number of things such as meeting diverse needs and considering the goals set by the government, following the applicable regulations, the wishes of the client, fulfilling media needs, sponsors’needs, community expectations and other matters. The need for a company engaged in the event organizing company to carry out an activity budget that is very important, so that it is more systematic and can save the cost of cash flow allocation activities and is always guided by the objectives of the event. Problems that are often experienced by companies CV. Active Production Makassar is not related to fixed costs and variable costs, so the company has difficulty determining the funs neded on accounts related to fixed costs and variable costs. From the calculation results using flexible budget variants, profits and the condition of the company’s financial flow can be predicted by making a draft budget for fixed costs and variable costs.